Food triggers and inherited metabolic disorders: a challenge to the pediatrician - Evelina Maines; Annunziata Di Palma; Alberto Burlina (BMC, 2018)
Abstract Several disorders should be considered in the case of newborns and infants experiencing acute or recurrent symptoms after food ingestion. Immune-mediated adverse food reactions are the most frequent and always to be considered. Nevertheless, in the extensive differential diagnosis, clinicians should also include inherited metabolic disorders (IMDs). This review reports clinical features and diagnostic aspects of the most common IMDs that may present with acute manifestations triggered by food intake. Major focus will be amino acid and protein metabolism defects and carbohydrate disorders. Nowadays, for many of these disorders the risk of an acute presentation triggered by food has been decreased by the introduction of expanded newborn screening (NBS). Nevertheless, clinical suspicion remains essential because some IMDs do not have still reliable markers for NBS and a false negative screening result may occur. The aim of this review is to help pediatricians to take these rare inherited disorders into account in the differential diagnosis of acute or recurrent gastrointestinal symptoms related to food intake, which may avoid delayed diagnosis and potentially life-threatening consequences.